Perilaku Petani Pada Program Pengembangan Klaster Padi Binaan Bank Indonesia (Kasus Subak Pulagan, Desa Tampaksiring, Kecamatan Tampaksiring, Kabupaten Gianyar) - DESAK AYU TRISNA SARI; I GEDE SETIAWAN ADI PUTRA; I DEWA PUTU OKA SUARDI (Agribusiness Study Program, Faculty of Agriculture, Udayana University, 2017)
The Behavior of Farmers on Rice Cluster Development Program AssistedInonesian Bank (Case of Subak Pulagan, Tampaksiring Village, TampaksiringDistrict, Gianyar Regency)Bank Indonesia has been mentoring and coaching in the pass program developmentreal sector and UMKM. The purpose of this study to knowledge, attitudes, and skillof farmers on rice cluster development program assisted Indonesian Bank. This study took place in Subak Pulagan with the number of respondents 48 people. Methods ofdata collection by interview and analyzed by qualitative descriptive analysis. The results showed the behavior of farmers on rice cluster development program is inexcellent condition with a score of 85,1%. It can be seen from the three indicators. Excellent knowledge indicators category with a score of 84,4%, a very good attitudeindicator categories premises a score of 84,7%, and very good indicator oh the skillcategory with a score of 86,2%.Advice which may be recommended that the diversification of products is not good,it can be suggested that extension is to provide an understanding of the impotance ofdiversification benefits of products to enhance the competitiveness and obtaineconomic value higher.